If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 5x + -4x Combine like terms: 5x + -4x = 1x 6 = 1x Solving 6 = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + -1x = 1x + -1x Combine like terms: 1x + -1x = 0 6 + -1x = 0 Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 6x-8=10x-28 | | -2=4k-6k | | 11/4r-9=4/7r | | X=-9/67 | | 2/3(6x-x)=5/6x | | -8(1-6k)+5k=8k+37 | | x+4x-3x+1=3 | | 8x^4-56x^3+98x^2=0 | | 892=d+828 | | 2x+7-4(x+1)=3x+7 | | 5/7-5/14 | | 28108.16=z*a | | 2/3*-4=10 | | 14x+10-8x=24-x | | 588=14f | | 8x^4-56x^3+92x^2=0 | | X-3/8=9/8 | | -2(5x+5)=6x-10 | | 26+n=78 | | x-16500=11608.16 | | 8(1-6n)=-7n+8 | | ln(1-4x)=6x | | 3a+7a^2= | | x-y=11608.16 | | 6(1-6x)=39-3x | | 3y=18-6z | | 5m+5b=80 | | 55m+5b=80 | | -6(p-7)=24+3p | | 0.00224t^2-1.5t+40*3.14=0 | | -4=r/20 | | (x-4)(x-9)=x^2+px+36 |